2013
DOI: 10.14214/sf.963
|View full text |Cite
|
Sign up to set email alerts
|

Estimating coarse roots biomass in young silver birch stands on post-agricultural lands in central Poland

Abstract: Estimating coarse roots biomass in young silver birch stands on post-agricultural lands in central Poland. Silva Fennica vol. 47 no. 2 article id 963. 14 p. Highlights • Age and size of the tree are the most important factors that influence the amount of belowground biomass. • Allocation of the biomass to the coarse roots also depends on age and size of the tree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
(78 reference statements)
0
16
1
Order By: Relevance
“…Tree stands of such secondary woods were probably composed of even-aged Alnus with Betula pendula and Betula pubescens in admixtures. In the understorey, Sambucus nigra and Salix were growing among other plants as is observed today (Bijak et al 2013). Additionally, alder expansion from the 1970s was enabled by the poor efficiency of local drainage causing the rise of ground water levels.…”
Section: The History Of Environmental Changesmentioning
confidence: 95%
See 1 more Smart Citation
“…Tree stands of such secondary woods were probably composed of even-aged Alnus with Betula pendula and Betula pubescens in admixtures. In the understorey, Sambucus nigra and Salix were growing among other plants as is observed today (Bijak et al 2013). Additionally, alder expansion from the 1970s was enabled by the poor efficiency of local drainage causing the rise of ground water levels.…”
Section: The History Of Environmental Changesmentioning
confidence: 95%
“…The spontaneous natural reforestation has become more and more important as the area of abandoned lands has increased in response to socio-economic changes that took place not only in the studied region but in whole of Central and Eastern Europe at the end of the last century (Bijak et al 2013;Młynkowiak and Kutyna 2009;Stanturf 2015;Zasada et al 2014). Low-intensity afforestation relying upon natural recolonization of abandoned fields and pastures has proven to be effective under the growing conditions of the whole Baltic region.…”
Section: The History Of Environmental Changesmentioning
confidence: 99%
“…We did not separate fine and coarse roots in this procedure. Because previous studies demonstrated that coarse roots, which have longer residence time than fine roots, made the predominant contribution to root biomass (IPCC 2006;Miller et al 2006;Bijak et al 2013;Smyth et al 2013), we assumed that disregarding fine and coarse roots is acceptable in terms of quantifying the total root biomass.…”
Section: Below-ground Biomassmentioning
confidence: 99%
“…Pietrzykowski andSocha (2011) analysed the size of pine's biomass on reclaimed habitats. Jagodziński and Kałucka (2011) and Bijak et al (2013) were estimating the belowground biomass of birch and pine in stands resulting from afforestation on agricultural lands. Worth noting are also Orzeł et al (2005Orzeł et al ( , 2006aOrzeł et al ( , 2006b thesis.…”
Section: General Assumptions For Estimation Of Woody Biomassmentioning
confidence: 99%
“…Mentioned authors distinguish above and below ground part of stump, including the above ground part to aboveground biomass. Similarly, Bijak et al (2013) to below ground biomass included only part of stump located below ground (root crown). Socha and Wężyk (2004) and Zasada et al (2008) did not precise unequivocally whether analysed by them trees were cut on ground level.…”
Section: Biomass Conversion and Expansion Factors (Bcef)mentioning
confidence: 99%